2020
DOI: 10.1007/s12282-020-01081-4
|View full text |Cite
|
Sign up to set email alerts
|

Annual report of the Japanese Breast Cancer Society registry for 2016

Abstract: The Japanese Breast Cancer Society (JBCS) registry began data collection in 1975, and it was integrated into National Clinical Database in 2012. As of 2016, the JBCS registry contains records of 656,896 breast cancer patients from more than 1400 hospitals throughout Japan. In the 2016 registration, the number of institutes involved was 1422, and the total number of patients was 95,870. We herein present the summary of the annual data of the JBCS registry collected in 2016. We analyzed the demographic and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…Accessory breast carcinoma in males is rare [1][2][3]. In addition to Maki et al's compilation of Japanese reports from 1996 to 2013 [4], we performed a journal search using "Men/accessory Breast Cancer" as keywords and found that from January 2014 to June 2020, only 26 cases of accessory breast cancer in males were reported in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accessory breast carcinoma in males is rare [1][2][3]. In addition to Maki et al's compilation of Japanese reports from 1996 to 2013 [4], we performed a journal search using "Men/accessory Breast Cancer" as keywords and found that from January 2014 to June 2020, only 26 cases of accessory breast cancer in males were reported in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Breast carcinoma in males accounts for just 0.6% of all malignant breast neoplasm cases in Japan [ 1 ]. The total incidence rate of accessory breast carcinoma is 0.2–0.6% [ 2 ], and males account for only 2.4–5.3% of accessory breast carcinoma cases, making it rare [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main treatment for breast cancer is surgery, which may include adjuvant radiation therapy, chemotherapy, and hormone therapy. As approximately 80% of Japanese breast cancer patients, especially older women (Sawaki et al, 2021), have hormonally receptive cancer (Kubo et al, 2020), hormone therapy for breast cancer is a common treatment in Japan. Aromatase inhibitors that are administered to older patients with breast cancer exert a therapeutic effect by lowering estrogen levels in the body in order to reduce the supply and stimulation of hormones and suppress the growth of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen receptor‐positive (ER+), epidermal growth factor 2‐negative (HER2−), and node‐negative (n0) breast cancers account for approximately half of invasive breast cancer in Japanese women 1 . As the report that individuals with invasive breast cancer measuring more than 1 cm derive a significant benefit from adjuvant chemotherapy regardless of nodal and ER status was published in 2000 (NIH), most patients with ER+/HER2−/n0 breast cancer have been treated with adjuvant chemotherapy 2 .…”
Section: Introductionmentioning
confidence: 99%